DNA methylation evidence against the accelerated aging hypothesis of schizophrenia - Brandon C. McKinney (Nature Portfolio, 2017)
Abstract The accelerated aging hypothesis of schizophrenia posits that physiological changes throughout the body that are associated with normal aging occur at an earlier age in individuals with schizophrenia. Testing this hypothesis has been limited by problems measuring biological age. Recently, a method using DNA methylation levels at 353 genomic sites to produce “DNA methylation age”, an estimate of tissue biological age, was described and validated. We used this method to test the hypothesis in the postmortem superior temporal gyrus of 22 non-psychiatric control and 22 schizophrenia subjects. DNA methylation age correlated with chronological age in both non-psychiatric control (r = 0.95, p < 0.0001) and schizophrenia subjects (r = 0.96, p < 0.0001). Age acceleration did not differ between non-psychiatric control and schizophrenia subjects (t = 1.27, p = 0.21). Our findings suggest there is no acceleration of brain aging in schizophrenia. Larger studies using samples from multiple brain regions and homogenous cell populations will be necessary to confirm these findings.